2019
DOI: 10.1002/apj.2298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of enhanced liquid mixing in T‐T mixer at various Reynolds numbers

Abstract: Passive mixers of planar geometry are most preferred for micro total analysis systems (μTAS) due to their low cost, ease of integration, and robustness. They are also widely employed chemical processing field as they incur very low processing costs. A simple passive T-mixer has been studied by many authors and used for various applications poor mixing at low Re (Re < 200) (laminar regime) and high Re (Re > 400) (pulsating vortex regime) is its main disadvantage respectively. This limitation is shown to be over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…This was due to the fact that the design of T–T mixer facilitates overlapping of vortices pertaining to different samples (Figure 8b), which is not possible with the design of T‐mixer as only one sample is allowed from each side (Figure 8a). A more detailed study on the comparison of mixing phenomenon of conventional T and T–T mixers can be found in Dundi et al 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the fact that the design of T–T mixer facilitates overlapping of vortices pertaining to different samples (Figure 8b), which is not possible with the design of T‐mixer as only one sample is allowed from each side (Figure 8a). A more detailed study on the comparison of mixing phenomenon of conventional T and T–T mixers can be found in Dundi et al 21 …”
Section: Resultsmentioning
confidence: 99%
“…They found a considerably improved mixing performance by T–T mixer at higher Re (flow rates greater than 8 ml min −1 ) compared to T‐mixer. Dundi et al 21 numerically evaluated the mixing phenomenon in T–T mixer and characterized the flow behavior of the device at various Re in the range of 0 to 700. It was observed that the T–T mixer design facilitates the use of symmetrical four‐vortex regime to the advantage of the mixing enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2. Grid independence study and validation (a) Average axial velocity profiles at outlet of T-micromixer for different meshes, (b) Mixing quality at outlet of T-micromixer for different meshes and (c) Comparison of Mixing quality with various Reynolds number for T-mixer of the present study and Dundi et al17 …”
mentioning
confidence: 79%
“…The governing equations of the flow field and species transport of the T-mixer have been solved in this study using conditions comparable to those used by Dundi et al 17 To validate the accuracy of the current numerical scheme, the results obtained were compared to the results of Dundi et al 17 Equations ( 4) and ( 5) were used to assess mixing quality at the T-mixer outlet. Figure 2(c) shows that the current study's findings are in close accord with those of Dundi et al 17…”
Section: Validationmentioning
confidence: 99%
“…It was found that the mixing effect can be improved when the apical angle of the triangle is increased. On the other hand, Dundi et al 27 studied the liquid mixing in a T–T mixer. Instead of having two inlets into the mixing channel, T–T mixer possesses four inlets, which is reported to have higher mixing performance over a wide range of Re (i.e., 0 < Re < 750).…”
Section: Introductionmentioning
confidence: 99%